Optimization of Media for Enhanced Glucoamylase Production in Solid-State Fermentation by Fusarium solani - Nawaz Bhatti, Haq (Array, 2007)
Solid-state cultivation of Fusarium solani was carried out for enhanced production of glucoamylase (GA) using different substrates like wheat bran, rice bran, green gram bran, black gram bran and maize bran. The SSF medium containing wheat bran as a substrate yielded the highest enzyme activity. The physical and chemical parameters were optimized. Maximum enzyme activity (61.35±3.69) U/g of dry wheat bran was achieved under optimum growth conditions. The optimum conditions were fructose as carbon and energy additive 1 % (by mass), urea as nitrogen additive 1 % (by mass), initial moisture content of solid substrate 70 % (by mass per volume), incubation period 96 h, inoculum size 15 % (by mass per volume) having 106–107 spores/mL, incubation temperature (35±1) °C and pH=5.0. It was further observed that the addition of surfactants caused a decrease in enzyme biosynthesis by F. solani in SSF of wheat bran under optimum process conditions